Fire Evacuation Process Using Both Elevators and Staircases for Aging People: Simulation Case Study on Personnel Distribution in High-Rise Nursing Home - Yameng Chen; Chen Wang; Jeffrey Boon Hui Yap; Heng Li; Hong Song Hu; Chih-Cheng Chen; Kuei-Kuei Lai (Discrete Dynamics in Nature and Society)
There were increasing concerns on the possibility and suitability of using elevators for high-rise building evacuation because, through the improvement of the elevator system, the self-evacuation ability of age people is promoted as much as possible in the process of an emergency evacuation. The combined evacuation using both elevators and stairs was put into discussion. However, there was no empirical evidence and numerical simulation on emergency evacuation using both elevators and staircases for aging people in high-rise nursing homes. Therefore, using one case study, this paper simulated the emergency evacuation in a high-rise nursing home using variables such as the distribution of the elderly with different physical conditions, the proportion of the elderly in different physical conditions, the number of the elderly, the number of floors, the number of elevators used, and the priority of the elevator floor. By simulating the evacuation process in various scenarios, the general distribution strategy of high-rise nursing home and the optimal use of the elevator-stair combination during the emergency evacuation were developed. Results show that the elevator-stair combination of evacuation is more effective than using elevators or stairs alone. Increasing the number and speed of elevators can reduce evacuation time. Categorizing elderly people on each floor according to their physical conditions could reduce the evacuation time than randomly distributing them.